Women’s migration and family structure: gender analysis based on the experience of Uzbekistan - Bakirova Oynura Norquchqor qizi (THE INNOVATION ECONOMY, 2026)
This article presents a gender-based analysis of the growing trends in female labor migration in Uzbekistan and examines the impact of migration processes on family structure and the socio-psychological state of society. The study highlights structural differences in the motivations of male and female migrants and scientifically substantiates the influence of migration on children, relatives, and the institution of marriage. The working and living conditions of female migrants, their access to healthcare and education, and existing challenges regarding legal protection and security are analyzed. The necessity of developing gender-sensitive migration policies is justified, with proposals made for adapting international best practices to the context of Uzbekistan. The research findings are aimed at strengthening gender equality and ensuring the sustainable development of migration processes.